Simulasi Pola Tanam (Agroforestri dengan Hortikultura) untuk Meningkatkan Produktifitas Lahan dengan Sistem Permakultur - Febri Afiantoro; Noordiana Herry Purwanti; Ila Purnamasari (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
This research is entitled "Simulation of Cropping Patterns (Agroforestry with Horticulture) to Increase Land Productivity with Permaculture System", which aims to develop an effective simulation method for designing cropping patterns in increasing permaculture land productivity and providing simulation results and their practical application in land design. This research was conducted from March to July 2024, located at Jalan Magelang Km 5.6, Kutu Tegal, Sinduadi, Mlati, Sleman, Special Region of Yogyakarta 55284. The simulation of cropping patterns was carried out using the SketchUp computational model and Andrew Marsh Simulation, and was evaluated based on aspects of the utilization of sunlight and plant growing space. Through this simulation method, the optimal combination of plants in the permaculture system was found. The simulation results were then analyzed and evaluated in the field to assess their success in increasing land productivity. Each cropping pattern shows unique characteristics in utilizing sunlight, growing space, and soil nutrients optimally, thus supporting more sustainable and productive land management.